1971
DOI: 10.1017/s0031182000077519
|View full text |Cite
|
Sign up to set email alerts
|

A study of acetylcholinesterase throughout the life cycle ofNippostrongylus brasiliensis

Abstract: Acetylcholinesterase activity, measured per unit wet weight, is relatively low in the eggs and infective larvae of N. brasiliensis. It increases rapidly during the parasitic phase, especially in the late 3rd- and early 4th-larval stages. Activity in normal adults is extremely high (× 15 egg activity) and this is doubled again in immune-damaged adults. Possible functions of N. brasiliensis acetylcholinesterase are discussed.It is a pleasure to acknowledge the technical assistance of Miss Anne Cronin and Miss Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1972
1972
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…24 Several hypotheses can explain the enhanced response to carbachol in post-infected rats in comparison with controls. It is known that N. brasiliensis produces very large amounts of acetylcholinesterase 25 which has been found to modulate the proliferation of epithelial cells. 26 We can suppose that the subsequent decrease in acetylcholine availability induces an up-regulation of muscarinic receptors which would explain the increased reactivity to carbachol.…”
Section: Discussionmentioning
confidence: 99%
“…24 Several hypotheses can explain the enhanced response to carbachol in post-infected rats in comparison with controls. It is known that N. brasiliensis produces very large amounts of acetylcholinesterase 25 which has been found to modulate the proliferation of epithelial cells. 26 We can suppose that the subsequent decrease in acetylcholine availability induces an up-regulation of muscarinic receptors which would explain the increased reactivity to carbachol.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo feeding significantly declined with helminth age, this repression being reversible as normal feeding rates are recovered in vitro (BOTTJER & BONE, 1985a). SANDERSON & OGILVIE (1971) showed that the level of acetylcholinesterase in N. brasiliensis does not remain constant throughout adult life but increases between 7 and 14 days post infection concurrently with the development of immunity by the host. Moreover, immune damaged worms had modified isoenzyme patterns of acetylcholinesterase (EDWARDS etal., 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Acetylcholinesterase is produced in the oesophageal and sub-ventral glands of N. brasiliensis (Sanderson, 1969;Lee, 1970) and is released into the environment of the worm (Ogilvie, Rothwell, Bremner, Schnitzerling, Nolan & Keith, 1973;Burt & Ogilvie, 1975). There is a 15-fold increase in the amount of AChE present in N. brasiliensis during the first 12 days of development from the egg to the sexually mature adult and this amount is doubled during the succeeding 7 days as the nematodes are rejected from the intestine (Sanderson & Ogilvie, 1971). Jones & Ogilvie (1972) suggested that antibodies produced by the host influence the amount of AChE synthesized by the worm, since nematodes which develop in rats given specific antisera, or adapted nematodes (that is, worms which mature in an immune host following a secondary, challenge infection) contain more AChE than normal worms.…”
Section: Discussionmentioning
confidence: 99%
“…The first stage of the rejection mechanism involves humoral antibodies which cause, directly or more likely indirectly, permanent degenerative changes in the cells of the reproductive tract, gut and sub-ventral glands of the worm (Ogilvie & Hockley, 1968;Lee, 1969). As the immune response develops there is also a well-marked increase in the amount of acetylcholinesterase (AChE), an enzyme produced by and released from the sub-ventral glands of this nematode (Lee, 1970;Edwards, Burt & Ogilvie, 1971;Sanderson & Ogilvie, 1971;Burt & Ogilvie, 1975). Although the humoral antibody response causes changes in the structure and physiology of N. brasiliensis and antibody-damaged nematodes are rejected more quickly than normal worms (Ogilvie & Hockley, 1968), the rejection of N. brasiliensis from the intestine of a well-nourished rat is dependent upon the involvement of sensitized lymphocytes (Keller & Keist, 1972;Ogilvie & Jones, 1973;Ogilvie & Love, 1974;Ogilvie, Love, Jarra & Brown, 1977).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation